A Functional Variant of CXCL16 Is Associated With Predisposition to Sepsis and MODS in Trauma Patients: Genetic Association Studies - Sun, Jianhui; Zhang, Huacai; Liu, Di; Cui, Li; Wang, Qiang; Gan, Lebin; Wen, Dalin; Wang, Jun; Du, Juan; Huang, Hong; Zhang, Anqiang; Deng, Jin; et al. (Frontiers in Genetics, 2021)
Purpose: CXC chemokines are mediators which mediate immune cells migration to sites of inflammation and injury. CXCL16 plays an important role in the occurrence and development of sepsis through leukocyte chemotaxis, leukocyte adhesion and endotoxin clearance.. In this study, we selected a set of tag SNPs in the CXCL16 gene and investigated their clinical relevance to the development of sepsis and multiple organ dysfunction syndrome (MODS) in patients with major trauma in three independent Chinese Han populations. Methods: A total of 1,620 major trauma patients were enrolled in this study. Among these patients, 920 came from Chongqing in western China, 350 came from Zhejiang Province in eastern China, and 350 came from Guizhou Province in southern China. The improved multiplex ligation detection reaction (iMLDR) method was employed in the genotyping and genetic association analyses to determine the associations between CXCL16 haplotypes and sepsis morbidity rate and higher MOD scores in three cohorts. Results: Only CXCL16 T123V181 haplotype was associated with an increased risk for sepsis morbidity and higher MOD scores in the three cohorts (OR = 1.89, 𝑃 = 0.001 for the Chongqing cohort; OR = 1.76, 𝑃 = 0.004 for the Zhejiang cohort; OR = 1.55, 𝑃 = 0.012 for the Guizhou cohort). The effect of T123V181 haplotype on the chemotaxis, migration and endotoxin clearance of immune cells were further observed. Protein modeling analysis showed that T123 and V181 might alter the structure of the CXCL16 active center. Thus it enhanced the chemotaxis and adhesion ability of immunocytes. Conclusion: We demonstrate the mechanism of CXCL16 T123V181 haplotype which regulates the sepsis morbidity rate and thus provide a new biomarker for early diagnosis of sepsis and MODS. Trial registration: ClinicalTrials.gov, NCT01713205.